Pion photoproduction on a deuteron at the VEPP-3 electron beam; Nuclear Instruments and Methods in Physics Research A; Vol. 1074 - Cherepennikov Yu. M. Yuriy Mihaylovich; Darwish E. M. Eed; Fiks (Fix) A. I. Alexander Ivanovich; Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Levchuk M. I. Mikhail Ivanovich; Loginov A. Yu. Aleksey Yurievich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Shestakov Yu. V. Yury Vadimovich; Shevelev M. V. Mihail Viktorovich; Toporkov D. K. Dmitry Konstantinovich; Yurchenko A. V. Aleksey Vasilievich; et al. (2025, 2025)
Title screen